THE EFFECT OF EMPLOYEES DEVELOPMENT AND SUPERVISION ON WORK EFFECTIVENESS IN THE DPRD SECRETARIAT OF THE NORTH SUMATERA PROVINCE - Asrizal Efendy Nasution; Muhammad Taufik Lesmana (AIBPM Publisher, 2019)
This study aims to determine the effect of employee development and supervision on the work effectiveness of employees of the DPRD Secretariat of North Sumatra Province. The method of data analysis is used quantitative descriptive method. Testing the hypothesis by using multiple linear regression analysis. Data analysis method using SPSS 20.0 for Windows. The data used are primary and secondary data. In this study, the population is all 30 North Sumatra Provincial DPRD Secretariat employees. Based on the results of the simultaneous significance test (F-Test), it shows that there is an influence of employee development (X1) and supervision (X2) on increasing employee work effectiveness (Y) at the North Sumatra Provincial DPRD Secretariat as evidenced by Ftest > Ftable 10,570>3,34 or the significance value < from α that is 0,000 ttable which is 3.225 >2,05183 or the significance value < α that is 0.003 ttable which is 3.578 > 2,05183 or the significance value < α that is 0.001